Strengthening Moderate Islamic Religiousness in Habib Husein Ja'far's Digital Da'wah - Mohammad Khafid Akhwanudin; Muhammad Kholilurrohman; Tiara Bela Fitriani; Dwi Nur Afiantiy; Shilfa Amelia; Genta Haru Purwanto (TATHO: International Journal of Islamic Thought and Sciences, 2024)
This qualitative research aims to identify the value of strengthening moderate Islamic religiosity in digital da'wah delivered by Habib Ja'far. Indicators of religious moderation in Indonesia as an analysis theory. Habib Ja'far's da'wah content in the Jeda Nulis channel entitled "Avenger: Endgame" is the primary data of this research.  The data was obtained using observation techniques. This study concludes that there is a value of strengthening moderate Islamic diversity in Habib Husein Ja'far's digital da'wah, including the value of nationalism in the teachings of hubbul wathon, the value of anti-radicalism in the teachings of hablumminannas, the value of tolerance in the teachings of respecting plurality as sunnatullah, the value of accommodating local cultural wisdom. This study shows that the mainstreaming of religious moderation can be disseminated through da'wah content in the digital space. This study has not identified the obstacles of digital da'wah in the internalisation of the formation of moderate Islamic religiosity by Habib Husein Ja'far.